South Africa's early experiment in social medicine: its pioneers and politics. - Marks, S (1997)
The election of a democratic, nonracial government in South Africa has moved the health needs of the majority of the population to center stage. In the search for precedents, health policymakers have turned to South Africa's pioneering of health centers and social medicine in the 1940s. This paper looks at the intellectual context in which these ideas were first developed; the particular political circumstances and relationships between doctors and the state in the late 1930s, which facilitated the establishment of health centers; the role that the health centers were intended to play in South Africa's wider postwar health plans; and the reasons for the centers' failure. Contrary to conventional wisdom, it argues that the failure of the health centers and the wider health plans predated the advent of the National Party to power in 1948, and resulted mainly from the marginalization of the centers as a low-cost option for the poor, which was itself a consequence of underfunding and the vested interests of local health authorities and private practitioners.